SLC15A4 Serves as a Novel Prognostic Biomarker and Target for Lung Adenocarcinoma - Huang, Hui; Wang, Junwei; Chen, Shibin; He, HongJiang; Shang, Yu; Guo, Xiaorong; Lou, Ge; Ji, Jingjing; Guo, Mian; Chen, Hong; Yu, Shan (Frontiers in Genetics, 2021)
Background SLC15A family members are known as electrogenic transporters that take up peptides into cells through the proton-motive force. Accumulating evidence indicates that aberrant expression of SLC15A family members may play crucial roles in tumorigenesis and tumor progression in various cancers, as they participate in tumor metabolism. However, the exact prognostic role of each member of the SLC15A family in human lung cancer has not yet been elucidated. Methods We investigated the SLC15A family members in lung cancer through accumulated data from TCGA and other available online databases by integrated bioinformatics analysis to reveal the prognostic value, potential clinical application and underlying molecular mechanisms of SLC15A family members in lung cancer. Results Although all family members exhibited an association with the clinical outcomes of patients with NSCLC, we found that none of them could be used for squamous cell carcinoma of the lung and that SLC15A2 and SLC15A4 could serve as biomarkers for lung adenocarcinoma. In addition, we further investigated SLC15A4-related genes and regulatory networks, revealing its core molecular pathways in lung adenocarcinoma. Moreover, the IHC staining pattern of SLC15A4 in lung adenocarcinoma may help clinicians predict clinical outcomes. Conclusion SLC15A4 could be used as a survival prediction biomarker for lung adenocarcinoma due to its potential role in cell division regulation. However, more studies including large patient cohorts are required to validate the clinical utility of SLC15A4 in lung adenocarcinoma.